Diagnostic value of ST-segment deviations during cardiac exercise stress testing: Systematic comparison of different ECG leads and time-points. (1st July 2017) - Puelacher, Christian; Wagener, Max; Abächerli, Roger; Honegger, Ursina; Lhasam, Nundsin; Schaerli, Nicolas; Prêtre, Gil; Strebel, Ivo; Twerenbold, Raphael; Boeddinghaus, Jasper; Nestelberger, Thomas; Rubini Giménez, Maria; et al.
Abstract: Background: Exercise ECG stress testing is the most widely available method for evaluation of patients with suspected myocardial ischemia. Its major limitation is the relatively poor accuracy of ST-segment changes regarding ischemia detection. Little is known about the optimal method to assess ST-deviations. Methods: A total of 1558 consecutive patients undergoing bicycle exercise stress myocardial perfusion imaging (MPI) were enrolled. Presence of inducible myocardial ischemia was adjudicated using MPI results. The diagnostic value of ST-deviations for detection of exercise-induced myocardial ischemia was systematically analyzed 1) for each individual lead, 2) at three different intervals after the J-point (J + 40 ms, J + 60 ms, J + 80 ms), and 3) at different time points during the test (baseline, maximal workload, 2 min into recovery). Results: Exercise-induced ischemia was detected in 481 (31%) patients. The diagnostic accuracy of ST-deviations was highest at + 80 ms after the J-point, and at 2 min into recovery. At this point, ST-amplitude showed an AUC of 0.63 (95% CI 0.59–0.66) for the best-performing lead I. The combination of ST-amplitude and ST-slope in lead I did not increase the AUC. Lead I reached a sensitivity of 37% and a specificity of 83%, with similar sensitivity to manual ECG analysis (34%, p = 0.31) but lower specificity (90%, p < 0.001). Conclusion: When using ECG stress testing for evaluation of patients with suspected myocardial ischemia, the diagnostic accuracy of ST-deviations is highest when evaluated at + 80 ms after the J-point, and at 2 min into recovery.